1998
DOI: 10.1063/1.367129
|View full text |Cite
|
Sign up to set email alerts
|

Strain relaxation and exciton localization effects on the Stokes shift in InAsxP1−x/InP multiple quantum wells

Abstract: Photoluminescence (PL) and optical absorption studies have been performed on strained-layer InAsxP1−x/InP (001) (x<0.27) multiple quantum wells grown by low pressure metal-organic vapor phase epitaxy. The series contains samples with both coherently strained and partially relaxed multilayers, where the relaxation is characterized by misfit dislocations. The PL transition line shape at low temperature and at low excitation intensity as well as the evolution of its peak energy with temperature are charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…At T = 10 K, the emission spectrum exhibits an asymmetric lineshape skewed to low energy due to localized states, as found in other materials. 20,21 With increasing T, carriers trapped on potential minima are thermally ionized and recombination occurs prevalently from extended states, which start dominating PL for T Ͼ 150 K. This is better evidenced in Figs. 1͑b͒ and 1͑c͒, where a power dependent study of PL is shown at T = 150 K and 180 K, respectively.…”
Section: Influence Of Bismuth Incorporation On the Valence And Conducmentioning
confidence: 72%
“…At T = 10 K, the emission spectrum exhibits an asymmetric lineshape skewed to low energy due to localized states, as found in other materials. 20,21 With increasing T, carriers trapped on potential minima are thermally ionized and recombination occurs prevalently from extended states, which start dominating PL for T Ͼ 150 K. This is better evidenced in Figs. 1͑b͒ and 1͑c͒, where a power dependent study of PL is shown at T = 150 K and 180 K, respectively.…”
Section: Influence Of Bismuth Incorporation On the Valence And Conducmentioning
confidence: 72%
“…The density of dislocation related defects that may scatter the excitons is probably very small. Similar work in InAsP/InP compressively strained heterostructures, 12 where there is a wider variation in strain relaxation and where the relaxation is the only parameter which is systematically varied, shows that the Stokes shift variation may be used to determine the onset of relaxation.…”
Section: Discussionmentioning
confidence: 79%
“…Recently, we have interpreted the low temperature PL transitions in InAsP/InP compressively strained MQWs in terms of recombination from excitonic band tail states. 12 We have used an analytical model for the PL line shape derived by Ouadjaout and Marfaing. 5 These authors derived a value of 3/2 for the exponent n.…”
Section: Introductionmentioning
confidence: 99%
“…These localized states could be due to composition fluctuation, QW width fluctuation or interface roughness. [18][19][20][21][22] The energy levels of these states lay inside the bandgap, so the photo-generated carriers would be trapped at those levels at low temperatures and then radiatively recombined. With increasing temperature, the carriers occupied at the localized states would thermally escape to higher energy states thereby the emission peak shifted to the shorter wavelength.…”
Section: Resultsmentioning
confidence: 99%